2020
DOI: 10.26442/00403660.2020.06.000769
|View full text |Cite
|
Sign up to set email alerts
|

Thermal heliox proteome. High-temperature heliox does not cause destruction of human respiratory system cells

Abstract: Aim. Conducting a pilot study to assess the effect of thermal heliox on the state of the respiratory tract by studying of the exhaled breath condensate protein composition before the thermal heliox procedure, immediately after and after three hours of relaxation Materials and methods. A comparative study of the exhaled breath condensates (EBC) protein composition of five non-smoking healthy donors was carried out. The EBC was taken before the respiratory procedure, immediately after a 20-minute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The study of the protein composition of the air condensate exhaled by the patient showed the safety of the use of thermoheliox [ 6 , 7 ]. We performed an experimental study of the kinetics of accumulation of specific antibodies (IgG, IgM) in patients affected by coronavirus.…”
mentioning
confidence: 99%
“…The study of the protein composition of the air condensate exhaled by the patient showed the safety of the use of thermoheliox [ 6 , 7 ]. We performed an experimental study of the kinetics of accumulation of specific antibodies (IgG, IgM) in patients affected by coronavirus.…”
mentioning
confidence: 99%